Applied statistics module - Norhafizah Moslim; Farahanim Misni; Noryanti Muhammad; Roslinazairimah Zakaria; Siti Roslindar Yaziz; Siti Zanariah Satari (Penerbit Universiti Malaysia Pahang, 2013)
This module is intended to faciliate teaching and learning of statistics courses in colleges and universities at degree level. It is specially tailored for students of science, engineering and technology